2008
DOI: 10.5483/bmbrep.2008.41.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel dehydrin gene from Codonopsis lanceolata and analysis of its response to abiotic stresses

Abstract: Dehydrins (DHNs) compose a family of intrinsically unstructured proteins that have high water solubility and accumulate during late seed development at low temperature or in water-deficit conditions. They are believed to play a protective role in freezing and drought-tolerance in plants. A full-length cDNA encoding DHN (designated as ClDhn) was isolated from an oriental medicinal plant Codonopsis lanceolata, which has been used widely in Asia for its anticancer and anti-inflammatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…There are also a poly-proline cluster located at residues 171-176 between the K1-and K2-segments and a lysine motif consisting of six residues (KKKKKK) at residues 103-108, which is speculated to function as a nuclear targeting signal sequence (NTS) (8). A search for transmembrane helices using TMHMMv2.0 did not detect any transmembrane helix in Podhn, suggesting it functions in the cytosol or nucleus rather than in membranes (9).…”
Section: Resultsmentioning
confidence: 99%
“…There are also a poly-proline cluster located at residues 171-176 between the K1-and K2-segments and a lysine motif consisting of six residues (KKKKKK) at residues 103-108, which is speculated to function as a nuclear targeting signal sequence (NTS) (8). A search for transmembrane helices using TMHMMv2.0 did not detect any transmembrane helix in Podhn, suggesting it functions in the cytosol or nucleus rather than in membranes (9).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the dried roots of C. lanceolata are often used as a type of "recovery pill" to aid those who are weakened by disease, surgery or other medical therapy, blood loss or other injury, or childbirth (Fratkin et al, 1974). The value of C. lanceolata can also be revealed by numerous studies of certain specific genes, such as fructose-1,6-bisphosphate aldolase and dehydrin, or chemical products, such as saponins, involved in regulation of environmental stress and its enthnopharmacological roles (Pulla et al, 2008). Nonetheless, the underlying mechanisms that account for C. lanceolata's ethnopharmacology, however, remain largely unexplained and require further investigation.…”
Section: Introductionmentioning
confidence: 98%
“…It has been demonstrated that accumulation of ClDhn mRNA is significantly induced in response to various abiotic stresses such as salt, wounding, chilling and light, at different time points within 4-48 hrs post-treatment (14). However, orthologous genes from different species sometimes exhibit different expression patterns.…”
Section: Introductionmentioning
confidence: 99%